RETINAL CHANGES IN PREGNANCY INDUCED-HYPERTENSION - ZADE, MANDAR; VEERAMANI, V. PANIMALAR A.; N., DIVYA; BHASKARAN, BINDU (International Journal of Current Pharmaceutical Research, 2021)
Objective: The aim is to determine the prevalence of retinal changes in Pregnancy Induced Hypertension (PIH) and its association with age, parity, proteinuria, blood pressureand severity of PIH. Methods: This is a tertiary hospital based Cross-Sectional study including all patients, clinically diagnosed with Pregnancy Induced Hypertension. General demographic details along with age, gravida, gestation period, proteinuria, blood pressure and severity of PIH were noted. Ophthalmic examination was performed and detailed fundus examination was done. Results: A total of 52 patients were included in this study. Their mean age was 24.9 y; 32 out of 52 patients were primigravida (61%) and 20 patients were multi gravida (39%). Out of 52 patients 34 (65.38%) had Gestational Hypertension, 16 (30.76%) had preeclampsia, and 2 (3.8%) had eclampsia. 3 (5.76%) out of 29 patients with BP<160/100 mmHg and 10 (19.23%) out of 23 patients with BP>160/100 mmHg had developed Hypertensive Retinopathy. Hypertensive Retinopathy was seen in 13 (25%). Proteinuria was seen in 10 (19.23%) patients ranging between+to+++on the dipstick. Conclusion: Statistically significant correlation between retinal changes and proteinuria, blood pressure and severity of Disease.The most important requisite in a case of Pregnancy Induced Hypertension is Fundoscopic examination of retina. The retinal vessels during PIH form a gateway to visualize changes in the body and placental vessels, and may play a key role in early detection and treatment of PIH for protection of the mother as well as the fetus.